Kirchen als Attraktionspunkte für ältere Reisende - Eine kritische Betrachtung der touristischen Besuchermotivation am Beispiel der Kirche St. Michaelis (Michel) in Hamburg - Kristina Sommer (IUBH Internationale Hochschule, 2020)
– Churches are places of faith, but also tourist attractions. Especially cultural tourists appreciate the church build-ings for their architecture and atmosphere. There are different types of tourists who are interested in culture and visiting churches. Within the framework of a quantitative study, the example of the Church of St. Michaelis (Michel) in Hamburg is used to investigate what motivates older travellers in particular to visit churches on holiday. The Michel is a landmark of the city of Hamburg and high investment sums are currently being planned to improve the use of space around the church, which should also influence the quality of stay of citizens and visitors in the city. Despite competition from the Elbe Philharmonic, the Michel is still perceived as a landmark of the city and is therefore on the sightseeing list of older citizens. They are motivated above all by their interest in culture and education and especially by their interest in churches and landmarks.
Keywords: 650; Kulturtourismus; Städtetourismus; Seniorentourismus; Kirchentourismus; Reisemotivation; Attraktionspunkte